Pengaruh Sistem Inaportnet dan Pengawasan Kegiatan Kapal terhadap Efektivitas Clearance In/Out oleh Kantor KSOP Kelas IV Tegal - Shaula Anindya Adenevlin; M Aji Luhur Pambudi; Ratna Kurnia Dewi (Politeknik bumi Akpelni, 2025)
This research is motivated by the importance of the Inaportnet System and the role of ship activity supervision to support the smoothness of ship Clearance in/out effectiveness. This study aims to determine the results of the Influence of the Inaportnet System and Ship Activity Supervision on the Effectiveness of Clearance in/out by the Tegal Class IV KSOP Office. This study uses a quantitative descriptive approach with the sample of this study being employees of the Tegal Class IV KSOP Office who are involved in ship Clearance in/out activities consisting of 40 people, in addition the F Test shows that the Inaportnet System and Ship Activity Supervision have a positive influence on the Effectiveness of Ship Clearance in/out with a calculated f value of 40.004> f tabel 3.25 with a significance value of 0.000, with an R value of 0.827, 68.4% is influenced by the Inaportnet System and Ship Activity Supervision, while 31.6% is influenced by other factors such as human resources and port conditions. Therefore, the combination of system digitalization and effective supervision is the key to improving the quality of services in the KSOP Class IV Tegal environment.